Gal9/Tim-3 expression level is higher in AML patients who fail chemotherapy - Paola Dama; Marshall Tang; Noreen Fulton; Justin Kline; Hongtao Liu (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Immune checkpoint pathways active in Acute Myeloid Leukemia (AML) patients, especially during the course of remission induction chemotherapy, have not been well studied. Although dominant in mediating T cell dysfunction in cancer, it is now well-accepted that interruption of PD-1/PD-L1 axes alone does not always completely restore T cell function, indicating the involvement of additional negative regulatory pathways, such as TIM-3/Gal-9, in promoting T cell exhaustion. Here, we characterized these pathways in AML patients enrolled in a phase I dose escalation trial that combined Selinexor, a Selective Inhibitor of Nuclear Export (SINE), with high-dose cytarabine (HiDAC) and mitoxantrone (Mito) (NCT02573363) as induction therapy. To monitor changes in expression of immune checkpoint receptors, multi-parameter flow cytometry was performed on peripheral blood and bone marrow biopsy specimens at diagnosis and following induction therapy in 26 AML patients. Expression of CD47, PD-L1, PD-L2 and Gal9 was assessed on CD34+ AML blasts, as well as on CD34− cell populations. In parallel, we evaluated expression of inhibitory (PD1, CTLA4, LAG3, TIM-3) and stimulatory (CD28, ICOS, CD137, OX40, CD40L, HLA-DR) co-receptors on CD4+ and CD8+ T cell subsets. Compared to baseline, the frequency of Gal9+ CD34− cells was significantly higher in patients with treatment failure (TF) than in those in complete remission (CR), and this finding correlated with increased TIM-3 expression on marrow-resident T cells in TF patients. Moreover, when we measured the expression level of PD-1 and TIM-3 in bone marrow samples compared to peripheral blood, TIM-3 was significantly higher in BM specimens. Our results suggest that targeting the Gal9/Tim-3 axis could be effective in combination with induction chemotherapy to increase the likelihood of complete remission in AML patients.